Study of Wind Speed and Wind Potential at Kagbeni, Thini and Palpa in Nepal - Gupta, Suresh Prasad; Adhikar, Binod; Yadav, Dhiraj Lal (Journal of Basic & Applied Sciences, 2021)
The primary objective of this paper is to study and analyze the wind characteristics and power potential at the three different places in Nepal. One year of wind speed data measured at 10 m and 20m height above ground level, provided by the Department of Alternative Energy Promotion Center, have been analyzed in this study. Direct use of data including the mathematics of probability and statistics has been applied to compute the wind power potential of the proposed sites with the occurrence of effective wind speed between cut-in and cut-out speed. The diurnal wind speed variation analysis of the three different sites showed that higher wind speed occurred during the daytime and reached a maximum at 3 PM whereas the lowest wind speed occurred after midnight and achieved a minimum at 7 AM to 8 AM. On basis of wind energy potential, Kagbeni has an annual potential energy of 3.98MWhr/m2 at 10m height and 4.82MWhr/m2 at 20m height while Palpa has the potential of 0.27MWhr/m2 and 0.36MWhr/m2 at the two heights with wind speed more or equal to 3m/s. Similarly, Thini has potential of 2.4MWhr/m2 and 2.9MWhr/m2 at 10m and 20m height on the limit of above wind speed. On the monthly basis, Kagbeni and Thini have the highest average wind speed in June whereas Palpa has in March and April. Likewise the highest value of wind speed at Kagbeni, Palpa and Thani are found as 22.53m/s and 21.75m/s; 17.66m/s and 17.11m/s, and 17.9m/s and 7.3m/s in April and March at heights of 10m and 20m respectively.